Antarctophthirus lobodontis Enderlein 1909 ... - Leonardi, Maria Soledad; Palma, Ricardo Luis (Zenodo, 2013)
Antarctophthirus lobodontis Enderlein, 1909 “ Antarctophthirus ogmorhini ” Neumann 1907: 13. Not Antarctophthirus ogmorhini Enderlein, 1906. In part. Antarctophthirus lobodontis Enderlein, 1909: 508, 510, figs KK–NN. Freund 1928: 20, figs 14–16; Ferris 1934: 488, fig. 284; Thompson & Plomley 1938: 116, 124; Clay 1940: 296; Hopkins 1949: 509; Ferris 1951: 73; Gressitt & Weber 1959: 447; King 1964: 137; Clay & Moreby 1967: 166, fig. 180; Clay & Moreby 1970: 220; Gressitt 1970: 329; Wolcott 1971: 608, fig. on page 607; Dailey & Brownell 1972: 541; Pilgrim 1974: 1031, fig. 3; Kim et al. 1975: 547; Murray 1976: 92, fig. 4.8; Ledger 1980: 206; King 1983: 203; Kim 1988: 108; Durden & Musser 1994a: 7; Durden & Musser 1994b: 141; Barker 1996: 236; Pajot 2000: 32; King 2005: 234; Palma 2010: 409. Antarctophthirius [sic] lobodontis Enderlein, 1909; Ass 1934: 103. Misspelling. Type host. Lobodon carcinophaga (Hombron & Jacquinot, 1842) —Crabeater seal. Type locality. Booth Wandel Island, ... : Published as part of Leonardi, Maria Soledad & Palma, Ricardo Luis, 2013, Review of the systematics, biology and ecology of lice from pinnipeds and river otters (Insecta: Phthiraptera: Anoplura: Echinophthiriidae), pp. 445-466 in Zootaxa 3630 (3) on page 452, DOI: 10.11646/zootaxa.3630.3.3, http://zenodo.org/record/221768 ...